Analysis of Common Beta-Thalassemia (β-Thalassemia) Mutations in East Java, Indonesia - Hernaningsih, Yetti; Syafitri, Yuli; Indrasari, Yulia Nadar; Rahmawan, Prafa Alif; Andarsini, Mia Ratwita; Lesmana, Indra; Moses, Emmanuel Jairaj; Abdul Rahim, Nur Arzuar; Yusoff, Narazah Mohd (Frontiers in Pediatrics, 2022)
Background: The frequency of the beta-thalassemia (β-thalassemia) gene in Indonesia range from 3 to 10%. However, in the East Java province, there is still limited information on the prevalence of β- thalassemia mutations in clinically diagnosed beta-thalassemia patients of East Java. Therefore, this study aimed to characterize β- thalassemia mutations in selected patients in the East Java province of Indonesia. Methods: This is an analytical observational study. Diagnosis of β- thalassemia was based on clinical presentation, complete blood count (CBC) and hemoglobin (Hb) electrophoresis. Blood specimens were taken from each patient in three EDTA tubes, were analyzed for CBC, Hb electrophoresis and processed for DNA extraction and subsequent polymerase chain reaction (PCR). Detection of mutations in HBB gene exons 1, 2, and 3 of the β- thalassemia gene as the common mutation in Indonesia was done using PCR followed by Sanger sequencing. Results: Thirty-three (n=33) participants were involved in this study with ages ranging from five (5) to 17 years of age comprising 19 females and 14 males. Their ethnic origins were Javanese (n=30) and Chinese (n=3). CBC results showed mean ± standard deviation for Hb, RBC, MCV, MCH, MCHC, RDW-CV were 81.2±7.0 g/L; 3.40±0.39 x109/L; 71.05±5.72 fL; 24.12±2.45 pg; 33.91±1.47 g/dL; 24.38±6.02 % respectively. Hb electrophoresis revealed that five (5) out of 33 participants had beta-thalassemia and 28 out of 33 participants had hemoglobinopathy (Hb) E/beta-thalassemia. Results of Sanger sequencing showed the following genotype variations in the samples: 12 (36.4%) with βCD26/βIVS-I-5; 6 (18.2%) with βCD26/βCD35; 3 (9.1%) with βCD26/βIVS-I-2; 2 (6.1%) with βCD27/28/βCD40; 2 (6.1%) with βIVS-I-1/βCAP+1; and βCD26/βIVS-I-1; βIVS-I-5/βCAP+1; βIVS-I-5/βCD35; βCD26/βCD37; βCD26/βCD15; βCD26/βCD40; βIVS-I-5/βCD19 in 1 (3%) sample respectively; and 1 (3%) had no abnormality detected in sequencing even though electrophoresis showed abnormality in the migration pattern. The βCD26/βIVS-I-5 mutation was found in samples that were noted to have Hb E/beta-thalassemia on Hb electrophoresis. Conclusion: The underlying genetic variations are heterogeneous in thalassemia patients in East Java which were 12 variants found. The most common variant was βCD26/βIVS-I-5 which all accounted for Hb E/beta-thalassemia on Hb electrophoresis. Furthermore, 28 out of 33 participants had hemoglobinopathy (Hb) E/beta-thalassemia.